Base legal do legítimo interesse: dinâmica normativa e o direito à proteção de dados pessoais - Azevedo, Daniel Sampaio de (2021)
This paper aims to understand the normative dynamics of the legal basis of legitimate interest in the face of the rights of those entitled to personal data protection, as provisioned by the General Data Protection Law or LGPD (Law No. 13,709 of August 18, 2018). In fact, the research seeks to answer the following question: does the normative dynamics of legitimate interest, as provided for in Articles 7, IX, 10 and 37 of the LGPD, guarantee legal certainty to the subjects of the legal relationship of treatment, in the sphere of their respective legal positions? To formulate the question in another way: can the normative dynamics of legitimate interest balance the freedom of the processing agent to make use of personal data for strictly economic purposes (without consent from the data subject) and, at the same time, guarantee the protection of the rights of the personal data subject? After a qualitative and documental research, based on a bibliographic review, not restricted to specific books on the theme, also using articles and academic works (dissertation) on related subjects, as well as the analysis of law bills and court decisions, an attempt was made to analyze and describe the context in which the LGPD is situated in time and in the needs, in principle divergent, of data processors and the holder of personal data. As a result, it was identified that, on the one hand, data protection, besides being a new right of personality distinct from privacy, is also a fundamental right, albeit implicitly, because of its recognition in the Brazilian normative scope was given by a decision of the Federal Supreme Court; on the other hand, the processing of personal data, according to the LGPD, is only allowed in limited hypotheses, usually related to public interest, except in the case of consent and legitimate interest. And, in the latter case, as observed in the literature review, it adopts subjective parameters in its definition. Nevertheless, the subjectivity of the legitimate interest precept – as identified – is supplanted by procedures (especially, the proportionality test) that the LGPD itself made available to the processing agent, so that it could freely process personal data without violating the rights of the data subject. Thus observed, it was concluded that the normative dynamics of legitimate interest, inserted in the context of the legal relationship of processing, while guaranteeing the exercise of economic freedom of the processing agent, for the use without consent of personal data, requires a series of obligations aimed at guaranteeing the legal positions of titular of personal data, especially when they prevail over economic freedom.